The Effect Of Company Size And Company Age On Financial Performance Of Banks Listed On The Indonesia Stock Exchange In 2024/2025 - Yusril Ihza Mahendra (Journal of Creative Power and Ambition (JCPA), 2026)
The Effect Of Company Size And Company Age On Financial Performance Of Banks Listed On The Indonesia Stock Exchange In 2024/2025